Igbo Phonological Interferences in the Acquisition of English Phonemes /ʌ/ and /eɪ/ in Charity Ekezie’s Contents - Aini Savitri; Deva Olivia Artapa; Anisah Durrotul Fajri (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
As a lingua franca, the acquisition of English as second and foreign language has been strongly influenced by the first language of the speakers. This influence which is commonly called interferences has been pronounced especially in the pronunciation where the second language production of speech is highly affected by the first language phonological inventory. The differences in the phonological system of Igbo spoken by Nigerian and English, thus, are interesting to be investigated due to the wide differences of both phonological systems. This research addresses phonological interferences of Igbo in the pronunciation of English vowels /ʌ/ and /eɪ/. A qualitative case study approach was conducted using Weinrich’s framework of phonological interference. The findings show that the realization of phoneme /ʌ/ experience under-differentiation in initial position where it is consistently substituted with /ɔ/. However, in medial position, it is variably substituted with /ɔ/ or /ə/, which indicates that other influences may be involved. Meanwhile, the substitution of the diphthong /eɪ/ demonstrates a clear case of actual phone substitution either in the medial position or in the final position. The sounds used for substitution are phonologically similar to the target diphthong, which indicates that the pattern of replacement is predictable rather than random. This systematic replacement of one phoneme with its closest L1 equivalent confirms that the observed interference is a direct case of actual phone substitution. The observed interference patterns, while consistent, are based on a limited dataset. Therefore, further research with a larger sample size is needed for generalization.